Technology Literacy and Digital Learning Media Design Competence among University Students - Puti Andam Dewi; Siska Yulia Rahmi (STIT Ahlussunnah Bukittinggi, 2026)
The rapid development of digital technology in the 21st century requires Islamic Education students as prospective educators to possess technological literacy skills in developing innovative and adaptive digital learning media. This study aims to analyze the effect of technological literacy on the ability of Islamic Education students to design digital learning media. The study employed a quantitative approach using a correlational method. The population consisted of 442 fifth-semester students of the Islamic Education Study Program, with a sample of 70 students selected randomly using the Slovin formula. Data were collected through questionnaires and analyzed using simple linear regression analysis. The results showed that technological literacy had a significant effect on students’ ability to design digital learning media, with a significance value of 0.000 < 0.05 and a coefficient of determination of 0.568. These findings indicate that technological literacy contributes 56.8% to students’ ability to design digital learning media. This study emphasizes the importance of strengthening technological literacy in teacher education programs to support the development of adaptive, creative, and professional digital pedagogical competencies in the era of digital educational transformation.